The Enlargement of EU Towards Eastern, Central and South Europe and Its Impact on the Third Mediterranean Countries - Angelos Kotios; Yiannis Saratsis (European Regional Science Association (ERSA), 2006)
The main purpose of this paper is to examine the impact of the latest and forthcoming EU enlargement on the Euro-Mediterranean relations. The answer cannot be simple and it depends on many factors, primary role amongst others has the institutional evolution of EU. For example, will the existing regime of the Euro-Mediterranean relations be sustained after the enlargement? What will the EU discussions for a European Constitution conclude to? The underlying conclusion is that a prediction on the future of Euro-Mediterranean relations is not an easy task. In this direction two main questions are raised. First, if and in what context are the Third Mediterranean Countries and the CEE Countries competitive to each other, in respect to the European Market and second what are the primary dangers for the Third Mediterranean Countries after the EU enlargement. The paper deals with these questions and presents some basic findings for the above.
Keywords: 330